Sounding Obsession: A discussion on sounds from a garage film. Issue 2 (1st August 2019) - Cumming, John; Potter, Martin
This article is a discussion piece that reflects on the authors' video article 'Obsession: Redux ‐ Sounds from a Garage-Film' (Cumming and Potter 2019) and the digitized soundtrack of co-author John Cumming's film Obsession (1985). The authors explore the processes of, and concepts behind, creating the original multi-layered analogue soundtrack for Obsession, an artefact of creative practice from a specific moment on film culture and of filmmaking within Melbourne 'post-punk' culture of the early 1980s. As a personal and self-reflexive work, the Obsession soundtrack is replete with memory, both personal and popular, local and global. It is a collection of oral objects ‐ an audio archive of live recordings and media samples made in Melbourne, Australia, between 1978 and 1985. The discussion piece revisits the Obsession soundtrack, alongside the redux of this film, in the context of contemporary literature and practice in sonic thinking. The representation of the self and relationships in sound is underpinned by Michel Chion's (1994) understanding of palimpsest and Raul Ruiz's (1995) ideas on poetic objects and shamanic films. The purpose of this investigation is to link sonic memories and subjective self-representation to specific practices of soundtrack composition and specific sites and moments of cultural history. The synthesis of concepts, methods and works that we examine here contributes to an emerging discourse around embodied and reflexive sound.